2016
DOI: 10.18632/oncotarget.10518
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of potential therapeutic targets in dedifferentiated liposarcoma

Abstract: Sarcomas are rare cancers with limited treatment options. Patients are generally treated by chemotherapy and/or radiotherapy in combination with surgery, and would benefit from new personalized approaches. In this study we demonstrate the potential of combining personal genomic characterization of patient tumors to identify targetable mutations with in vitro testing of specific drugs in patient-derived cell lines. We have analyzed three metastases from a patient with high-grade metastatic dedifferentiated lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…validated the FRS2 amplification in DDLs (14 of 15, 93%) and found that the FGFR/FRS2 pathway was activated in 75% of high‐grade liposarcomas . Most recently, another study detected FRS2 amplification in the metastatic tumours of a DDL patient …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…validated the FRS2 amplification in DDLs (14 of 15, 93%) and found that the FGFR/FRS2 pathway was activated in 75% of high‐grade liposarcomas . Most recently, another study detected FRS2 amplification in the metastatic tumours of a DDL patient …”
Section: Introductionmentioning
confidence: 87%
“…24 Most recently, another study detected FRS2 amplification in the metastatic tumours of a DDL patient. 25 To evaluate more clearly the frequency of FRS2 amplification in ALT/WDL/DDL and understand the tumorigenic mechanism underlying this entity further, we analysed a large series of ALT/WDL/DDL at one of the largest medical centres in China. To our knowledge, this is the largest cohort in the English language literature.…”
Section: Introductionmentioning
confidence: 99%
“…Supernatants were incubated with 300 μl StreptavidinSepharose High Performance for 2 hours. Beads were collected and washed twice for 5 minutes at 4°C in 1% Triton X-100, 500 mM NaCl, 1 mM EDTA, twice for 5 min at 4°C in PBS with 0.1% Triton X-100, twice for 5 minutes at room temperature in 2% SDS, twice for 9 5 minutes at room temperature in 6 M Urea in PBS, and six times for 5 minutes at room temperature in 1 M NaCl, 25% Acetonitrile and twice for 5 min at room temperature in 20%…”
Section: Affinity Capture Of Biotinylated Proteinsmentioning
confidence: 99%
“…There have also been reported effects of FGFR inhibitors in osteosarcoma cells without apparent FGFR aberrations, indicating that other mechanisms for FGFR vulnerability exist (9,13). To increase the impact of FGFR inhibitors, it is crucial to understand in detail how their action on FGFR signaling and cell viability is determined.…”
Section: Introductionmentioning
confidence: 99%
“…osteosarcoma, rhabdomyosarcoma (RMS) and soft tissue sarcoma) (Weekes et al, 2016, Guagnano et al, 2012, Taylor et al, 2009, Chudasama et al, 2016, Zhou et al, 2016). In addition, the FGFR-specific downstream signalling adaptor, the FGFR substrate 2 (FRS2), is overexpressed in liposarcoma and render these cells sensitive to FGFR inhibitors (Hanes et al, 2016, Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%